Greek nursing students' immunization coverage: Data from central continental Greece - Deltsidou, Anna; Tsaprounis, Taxiarchis; Gesouli, Eftihia; Noula, Maria; Raftopoulos, Vasilios (My University, 2008)
Abstract Nursing students are at risk of acquiring vaccine-preventable diseases. To estimate the vaccination rates for nursing students, a cross-sectional survey was conducted in a major district of central continental Greece with an anonymous and self-administered questionnaire in a sample of 432 nursing students (the response rate was 97%). The eligible nursing students completed the questionnaire after informed consent was obtained. The vaccination rates of the nursing students ranged from 65.2% for the oral polio (SABIN) vaccine and 65.7% for the hepatitis B virus vaccine to 74.6% for the diphtheria-tetanus-pertussis (DTP) vaccine. The parents' level of education did not correlate with the students' underimmunization. The t-test showed that the senior students were more knowledgeable about the compulsory vaccines. Almost half of the nursing students were somewhat satisfied with the available information on vaccination, while 9.5% were not at all satisfied and 38.5% were underimmunized. The proportion of male students who had completed the SABIN and DTP vaccination schedules was higher compared to the female students. More health education programs could increase the vaccination rates among nursing students.
Keywords: Nursing students; Measles; Immunization; Hepatitis B vaccine; Pertussis vaccine; Tetanus; Diphtheria